2008
DOI: 10.1002/cpa.20243
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous energy transport in the FPU‐β chain

Abstract: We consider the energy current correlation function for the FPU-β lattice. For small non-linearity one can rely on kinetic theory. The issue reduces then to a spectral analysis of the linearized collision operator. We prove thereby that, on the basis of kinetic theory, the energy current correlations decay in time as t −3/5 . It follows that the thermal conductivity is anomalous, increasing as N 2/5 with the system size N .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
87
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 12 publications
14
87
0
Order By: Relevance
“…Without the stochastic shot noise, this is the well known Fermi-Pasta-Ulam model in contact with heat reservoirs at its ends, which was studied numerically by Lepri et al [2] who found a superdiffusive transport of heat implying an anomalous Fourier's law. This important result has been confirmed by other numerical studies and other approaches [4,8,12,14,15,17,18,23,29] The impulsive stochastic shot noise that we use here can be regarded as a procedure that turns the superdiffusive transport of heat into a diffuse transport leading thus to Fourier's law.…”
Section: Introductionsupporting
confidence: 77%
“…Without the stochastic shot noise, this is the well known Fermi-Pasta-Ulam model in contact with heat reservoirs at its ends, which was studied numerically by Lepri et al [2] who found a superdiffusive transport of heat implying an anomalous Fourier's law. This important result has been confirmed by other numerical studies and other approaches [4,8,12,14,15,17,18,23,29] The impulsive stochastic shot noise that we use here can be regarded as a procedure that turns the superdiffusive transport of heat into a diffuse transport leading thus to Fourier's law.…”
Section: Introductionsupporting
confidence: 77%
“…In fact, the arguments given at the beginning of this paragraph directly give this (putting a = 5/3), and one does not need to find C(t). The kinetic theory approach has been made more rigorous by the work of Lukkarinen and Spohn [96]. They also work with the linearized collision operator and make the relaxation time approximation, and for the quartic FPU chain they confirm the result in [95], namely C(t) ∼ t −3/5 .…”
Section: Kinetic and Peierls-boltzmann Theorymentioning
confidence: 90%
“…In [2], [24], [20] [29] a kinetic limit is performed for chains of an-harmonic oscillators, and in [23] a linear Boltzmann equation is rigorously derived for the harmonic chain of oscillators with random masses. In [5] the authors consider a system of harmonic oscillators in ∂ t u α (t, r,k) + v(k) · ∇u α (t, r, k)…”
Section: Introductionmentioning
confidence: 99%